Persistent moderate-to-weak mediterranean Diet adherence and Low scoring for plant-based foods across several southern european countries: are we overlooking the mediterranean diet recommendations? - Quarta, Stefano (2021)
The Mediterranean diet (MD) has been sponsored worldwide as a healthy and sustainable diet. Our aim was to update and compare MD adherence and food choices across several Southern European countries: Spain (SP), Portugal (PT), Italy (IT), Greece (GR), and Cyprus (CY) (MED, Mediterranean), and Bulgaria (BG) and the Republic of North Macedonia (NMK) (non-MED, non-Mediterranean). Participants (N = 3145, ≥18 y) completed a survey (MeDiWeB) with sociodemographic, anthropometric, and food questions (14-item Mediterranean Diet Adherence Screener, 14-MEDAS). The MED and non-MED populations showed moderate (7.08 ± 1.96) and weak (5.58 ± 1.82) MD adherence, respectively, with significant yet small differences across countries (SP > PT > GR > IT > CY > BG > NMK, p-value < 0.001). The MED participants scored higher than the non-MED ones for most of the Mediterranean-typical foods, with the greatest differences found for olive oil (OO) and white meat preference. In most countries, ≥70% of the participants reported quantities of red meat, butter, sweet drinks, and desserts below the recommended cutoff points, whereas <50% achieved the targets for plant-based foods, OO, fish, and wine. Being a woman and increasing age were associated with superior adherence (p-value < 0.001), but differences were rather small. Our results suggest that the campaigns carried out to support and reinforce the MD and to promote plant-based foods have limited success across Southern Europe, and that more hard-hitting strategies are needed.